PENGARUH KOMPENSASI DAN BEBAN KERJA TERHADAP KEPUASAN KERJA DAN DAMPAKNYA PADA KINERJA PEGAWAI PADA BADAN PERENCANAAN PEMBANGUNAN DAERAH PROPINSI SULAWESI TENGAH - Pontoh, Farham M (Katalogis, 2014)
The purpose of this study is to find out : (1) the influence of compensation  to job satisfaction;(2) the influence of work-load to job satisfaction; (3) the influence of job satisfaction to employee performance; (4) the influence of compensation to employee performance and (5) the influence of work-load to employee performance of Central Sulawesi Regional Development Planning Board employees.  The  population  of  this  research  is  the  employees  of  Central  Sulawesi  Regional Development Planning Board. According to the data from administration and human resource division, the amount employeeof Central Sulaw